Potential Use of Salivary Markers for Longitudinal Monitoring of Inflammatory Immune Responses to Vaccination - Pei Wen Lim; Johan Garssen; Elena Sandalova (Hindawi Limited, 2016)
Vaccination, designed to trigger a protective immune response against infection, is a trigger for mild inflammatory responses. Vaccination studies can address the question of inflammation initiation, levels, and resolution as well as its regulation for respective studied pathogens. Such studies largely based on analyzing the blood components including specific antibodies and cytokines were usually constrained by number of participants and volume of collected blood sample. Hence, blood-based studies may not be able to cover the full dynamic range of inflammation responses induced by vaccination. In this review, the potential of using saliva in addition to blood for studying the kinetics of inflammatory response studies was assessed. Saliva sampling is noninvasive and has a great potential to be used for studies aimed at analysing the magnitude, time course, and variance in immune responses, including inflammation after vaccination. Based on a literature survey of inflammatory biomarkers that can be determined in saliva and an analysis of how these biomarkers could help to understand the mechanisms and dynamics of immune reactivity and inflammation, we propose that the saliva-based approach might have potential to add substantial value to clinical studies, particularly in vulnerable populations such as infants, toddlers, and ill individuals.